Introduction of Pines in Tamil Nadu - Ponnuswamy, P. K. (Indian Forester, 1982)
Trials with tropical pines have been taken up in the state of Tamil Nudu for the last few years. In the altitudinal zone below 1100 m with rainfall 1000 mm or less Pinus caribaea has been tried but the conclusions cannot be drawn yet; in the altitudinal zone 1050-1250 m which has a rainfall 1100-1200 mm Pinus caribaea appears to be the best choice followed by P. kesiya though at Topsiip Pinus radiata grows quite fast. In the higher hills in the Pains and Nilgiris P. patula has already established itself as an outstanding species and is now being raised in conjuction with kumri crop for afforestation of forestry localities. Nearly 2,000 ha have already been planted with P. potula. The spacing used with kumri is 3.5 m Ã— 3.5 m. A mean annual increment of 20 ms per ha per year is expected at a rotation of 15 years. 120 candidates have been selected and 31 approved as plus trees till now for Pinus patula. A germplasm bank has been established and another is being raised. Top cleft grafting of tender shoots on 1 to 2 year old stock (container seedlings) has given 85% success.